2021
DOI: 10.3390/cancers13020229
|View full text |Cite
|
Sign up to set email alerts
|

Adenosinergic Pathway: A Hope in the Immunotherapy of Glioblastoma

Abstract: Brain tumors comprise different types of malignancies, most of which are originated from glial cells. Glioblastoma multiforme (GBM) is the most aggressive type of brain tumor with a poor response to conventional therapies and dismal survival rates (15 months) despite multimodal therapies. The development of immunotherapeutic strategies seems to be necessary to enhance the overall survival of GBM patients. So far, the immunotherapies applied in GBM had promising results in the primary phases of clinical trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 138 publications
(182 reference statements)
0
12
0
Order By: Relevance
“…AR activation contributes to tumor growth and formation of metastases [125,[134][135][136][137], notably by increasing T-cell anergy or promoting T-regs [138,139]. Interestingly, triggering AR can result in an increased expression of immune checkpoints such as CTLA-4, PD-1, LAG-3, and TIM-3 on CD8 + T-cells [140]. Several pre-clinical studies have demonstrated the synergistic effect of anti-PD-1 or anti-PD-L1 treatments in combination with the use of anti-CD73 antibodies.…”
Section: Exosomes and Cd73/cd39mentioning
confidence: 99%
“…AR activation contributes to tumor growth and formation of metastases [125,[134][135][136][137], notably by increasing T-cell anergy or promoting T-regs [138,139]. Interestingly, triggering AR can result in an increased expression of immune checkpoints such as CTLA-4, PD-1, LAG-3, and TIM-3 on CD8 + T-cells [140]. Several pre-clinical studies have demonstrated the synergistic effect of anti-PD-1 or anti-PD-L1 treatments in combination with the use of anti-CD73 antibodies.…”
Section: Exosomes and Cd73/cd39mentioning
confidence: 99%
“…Neoantigen vaccines are extensively investigated in melanoma and glioblastoma with promising results in increasing patients' survival (173)(174)(175). Given that glioblastoma has a low mutational and neoantigenic burden (8,176,177), these results suggest that neoantigen-based vaccines are effective even in tumors with low mutation rates such as pMMR/MSI-L (64,175). Neoantigen vaccines may improve the infiltration of immune cells into CRCME and increase the immunoscore of tumors, leading to increased tumor responses to ICIs and other immunotherapies (64).…”
Section: Cancer Vaccinesmentioning
confidence: 99%
“… On the left, an illustration of the different cell populations composing glioblastoma and its microenvironment, as well as associated blood-brain barrier disruption. On the right, a summary of the different areas covered by the articles in this Special Issue: GBM cells, stem cells, and preclinical studies [ 2 , 3 , 4 , 5 , 6 ], clinical studies [ 7 , 8 ], immunotherapy and new treatments [ 9 , 10 , 11 , 12 ]. Created with BioRender.com.…”
Section: Figurementioning
confidence: 99%
“…Eleven papers are included in this issue [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], and they range from in vitro and preclinical studies to clinical studies, and to immunotherapy and new potential treatments for glioblastomas ( Figure 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation